HUBUNGAN HIGIENE PENJAMAH DENGAN KUALITAS MIKROBIOLOGIS PADA MINUMAN ES COKLAT DI KOTA SEMARANG (Studi di Kecamatan Tembalang Dan Kecamatan Pedurungan) - Dwi Rahayuningsih; Martini Martini; Susiana Purwantisari; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Water borne disease is a disease caused by the entry of pathogenic bacteria in the body with drinks. Ice chocolate currently many outstanding in the community. Tembalang and Pedurungan, Semarang are an educational area so it is a strategic place to sell ice chocolate. The purpose of this research is to analyze relations between hygiene sanitation with microbiological quality in ice chocolate in Semarang (Study in Tembalang and Pedurungan). This study is observational-analytic with using cross sectional design. The samples were 38 samples of ice chocolate. Data were analyzed using Chi square. The results showed that most of the ice chocolate did not qualify with 35 samples (92,1%) of unqualified Coliform status, 21 samples (55,3%) were contaminated with Escherichia coli, and 6 samples (15,7%) were contaminated with yeast / mold / fungi. This study shows there is an relations between hygiene handlers with microbiological quality in ice chocolate (p value = 0,043). Traders should pay attention to hygiene when making ice chocolate so that bacterial contamination can be minimized.